Trends and Correlates of Cannabis-involved Emergency Department Visits: 2004 to 2011. Issue 6 (November 2016) - Zhu, He; Wu, Li-Tzy
Abstract : Objectives: To examine trends and correlates of cannabis-involved emergency department (ED) visits in the United States from 2004 to 2011. Methods: Data were obtained from the 2004 to 2011 Drug Abuse Warning Network. We analyzed trend in cannabis-involved ED visits for persons aged ≥12 years and stratified by type of cannabis involvement (cannabis-only, cannabis-polydrug). We used logistic regressions to determine correlates of cannabis-involved hospitalization versus cannabis-involved ED visits only. Results: Between 2004 and 2011, the ED visit rate increased from 51 to 73 visits per 100, 000 population aged ≥12 years for cannabis-only use ( P value for trend = 0.004) and from 63 to 100 for cannabis-polydrug use ( P value for trend < 0.001). Adolescents aged 12–17 years showed the largest increase in the cannabis-only-involved ED visit rate (rate difference = 80 per 100, 000 adolescents). Across racial/ethnic groups, the most prevalent ED visits were noted among non-Hispanic blacks. Among cannabis-involved visits, the odds of hospitalization (vs ED visits only) increased with age strata compared with age 12 to 17 years. Conclusions: These findings suggest a notable increase in the ED visit numbers and rates for both the use of cannabis-only and cannabis-polydrug during the studied period, particularly among young people and non-Hispanic blacks. Abstract : Supplemental Digital Content is available in the text